Bucu Kendit as a Socio-Religious Practice in the Life of the Senori Community, Tuban - Nur Aida Fitria Kusuma Putri; Siska Nirmala; Hanan Urwatin Nichla; Nurul Hakim (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
This study aims to analyze the continuity of socio-religious practices in the Bucu Kendit tradition within the community of Senori, Tuban, with a focus on its functions, values, and relevance amid the currents of modernization. The research employs a qualitative approach, with data collection techniques including observation, interviews, and documentation. Observation is conducted to directly understand the process of implementing the tradition, while interviews are carried out with community leaders and practitioners to explore the meanings and values embedded within it. Documentation is used to complement the data in the form of records and related archives. The findings reveal that the Bucu Kendit tradition not only serves as a cultural ritual but also functions as a means of social integration, a medium of community communication, and a reinforcement of spirituality through practices of prayer and expressions of gratitude to Allah SWT. Furthermore, this tradition embodies values such as mutual cooperation, solidarity, unity, and the internalization of religious values that contribute to shaping the character of the community. Amid the challenges of globalization, this tradition remains relevant as a cultural safeguard and a form of cultural da'wah that adapts to contemporary developments. The novelty of this research lies in its comprehensive analysis based on field data, integrating the social, religious, and educational aspects of the Bucu Kendit tradition as a model of local wisdom in strengthening the socio-religious resilience of modern society.